Pengaruh Kualitas Pelayanan dan Kepercayaan terhadap Loyalitas Konsumen Belanja Online Shopee pada Mahasiswa Fakultas Hukum dan Ekonomi Bisnis Universitas Dharmas Indonesia (UNDHARI) - Selvitri, Sri Reski; Resty, Fenisi; Wiska, Mayroza (ARZUSIN, 2023)
Study this conducted for knowing influence like what the impact caused by Influence Quality Service and Trust to Loyalty Consumer Shopee Online Shopping for Students of the Faculty of Law and Business Economics, Dharmas Indonesia University (UNDHARI). Research objectives this conducted for know and analyze as well as knowing the influence of Quality Service and Trust to Loyalty Consumer Shopee Online Shopping. Methods of analysis in research this is method quantitative with data retrieval using questionnaire. Data Analysis Techniques with Validity Test, Instrument Reliability Test, Correlation Analysis, Hypothesis Testing, Multiple Regression Analysis, Classical Assumption Test, Multiple Linear Regression Analysis. who became population in study this that is as many as 161 respondents and the sample in study this that is as many as 115 respondents who are Student / I Faculty of Law and Business Economics, University of Dharmas Indonesia (UNDHARI). Based on results research that has been done by researcher could collect _ that Quality Service positive and significant effect on the dependent variable, namely Loyalty Consumer Shopee Online Shopping . other than that there is influence positive and significant Among variable Trust to Loyalty Consumers at Universitas Dharmas Indonesia (UNDHARI) Students. Based on F test results obtained results that Quality Service (X1) and Trust (X2) have an effect significant by simultaneous to Loyalty Consumer Shopee Online Shopping (Y).